Information on Covid-19 and Effortful Control Level: Increasing or Decreasing Anxiety? - Hurriyati, Evi Afifah; Afriza, Sabilla; Fitriana, Efi; Cahyadi, Surya; Srisayekti, Wilis (International Journal of Criminology and Sociology, 2021)
Anxiety has increased with more information about the COVID-19 outbreak. The COVID-19 information can make people more aware and care about this pandemic. However, it also can make people feel panic and anxious. Emotional induction in the information is referring to how the emotion carried by the information can affect early adult’s anxiety, but the differences in effortful control level that each person has also define the level of anxiety someone experiences. The anxiety level related to effortful control is one dimension of temperament. This study is conducted in concern of the effect of emotional induction in COVID-19 information towards anxiety in high and low effortful control groups. This study used a quantitative method with quasi-experimental research. This study involves 218 early adults in an age range of 20-40 years old. This study used pictures from content information about COVID-19, Self-Assessment Manikin (SAM), Beck Anxiety Inventory (BAI), and Effortful Control Questionnaire (ECQ) as the measuring tools. The results of the significance test show p <0.005. This means that there is an effect of emotional induction on anxiety at both high and low effortful control levels. This study shows that emotional induction in the form of COVID-19 information reduces anxiety in the respondent group with a high level of effortful control, but increases anxiety in the respondent group with a low level of effortful control. The effect of COVID-19 information on anxiety based on effortful control in the late adult (over 65 years old) group, in this study cannot be explained.